The phosphatase calcineurin regulates pathological TDP-43 phosphorylation - Liachko, Nicole F. (Acta Neuropathol, 2016)
Detergent insoluble inclusions of TDP-43 protein are hallmarks of the neuropathology in over 90% of amyotrophic lateral sclerosis (ALS) cases and approximately half of frontotemporal dementia (FTLD-TDP) cases. In TDP-43 proteinopathy disorders, lesions containing aggregated TDP-43 protein are extensively post-translationally modified, with phosphorylated TDP-43 (pTDP) being the most consistent and robust marker of pathological TDP-43 deposition. Abnormally phosphorylated TDP-43 has been hypothesized to mediate TDP-43 toxicity in many neurodegenerative disease models. To date several different kinases have been implicated in the genesis of pTDP, but no phosphatases have been shown to reverse pathological TDP-43 phosphorylation. We have identified the phosphatase calcineurin as an enzyme binding to and catalyzing the removal of pathological C-terminal phosphorylation of TDP-43 in vitro. In C. elegans models of TDP-43 proteinopathy, genetic elimination of calcineurin results in accumulation of excess pTDP, exacerbated motor dysfunction, and accelerated neurodegenerative changes. In cultured human cells, treatment with FK506 (tacrolimus), a calcineurin inhibitor, results in accumulation of pTDP species. Lastly, calcineurin co-localizes with pTDP in degenerating areas of the central nervous system in subjects with FTLD-TDP and ALS. Taken together these findings suggest calcineurin acts on pTDP as a phosphatase in neurons. Furthermore, patient treatment with calcineurin inhibitors may have unappreciated adverse neuropathological consequences.